ISLAMIC RELIGIOUS COPING AND PROBLEMATIC-INTERNET USE WITH SELF-CONTROL IN COVID-19 PANDEMIC - Roudhotina, Wardah; Uyun, Qurotul (Psikis : Jurnal Psikologi Islami, 2022)
This study aimed to observe the correlation between the Islamic Religious Coping and the Problematic Internet Use (PIU) with the self-control as the mediator variable towards the university students in the COVID-19 pandemic. This study used purposive sampling technique, involved 304 active university students, male and female, 17 to 26 years old, muslim, and currently undergoing online learning. It used Iranian Religious Coping (IRCOPE) scale, Self-Control Scale (SCS), and Generalized Problematic Internet Use-2 (GPIUS-2) that have been adapted into Indonesia language. The data analysis method used is SEM analysis using the path analysis model with AMOS 26.0. It showed that Islamic religious coping had a direct effect on self-control (p=***; 0.300) and self-control could impact the problematic internet use indirectly (p=***; -0.226). However, the Islamic religious coping was not able to impact the problematic internet use (p=0.229; -0.70). This showed that the hypothesis was accepted as self-control could be the full mediator variable towards the problematic internet use.